AOT reverse micelles as versatile reaction media for chitosan nanoparticles synthesis - Orellano, María Soledad (2017)
It is known that Chitosan (Ch) can be used in several applications, such as antimicrobial agent or as drug delivery agent. However, being its water dispersibility very low at physiological pH it is necessary to find a way to improve it. One attractive strategy is to synthesize Chitosan Nanoparticles (Ch-NPs). In this work, a versatile method to obtain Ch-NPs with different and controlled sizes, that were successfully prepared by cross-linking reaction of glutaraldehyde and native chitosan inside of n-heptane/sodium 1,4-bis-2-ethylhexylsulfosuccinate (AOT)/water reverse micelles (RMs) is presented. Highly monodisperse NPs were synthesized as confirmed by Dynamic Light Scattering (DLS) and Scanning Electron Microscopy (SEM) techniques. The particle size was dependent on the reactants concentration, cross-linking degree and mainly the amount of water inside of the AOT RMs used as nanoreactors. While the cross-linking is quite difficult to control in bulk water, the reaction inside the RMs is more manageable and efficient.